1984
DOI: 10.1523/jneurosci.04-03-00860.1984
|View full text |Cite
|
Sign up to set email alerts
|

Development of hyperpolarizing inhibitory postsynaptic potentials and hyperpolarizing response to gamma-aminobutyric acid in rabbit hippocampus studied in vitro

Abstract: The postnatal development of IPSPs and response to locally applied GABA were examined using intracellular recording techniques in region CA1 of rabbit hippocampal slices maintained in vitro. Pyramidal neurons in slices from mature rabbits demonstrated an EPSP-IPSP sequence following stimulation of stratum radiatum. In these same slices, pressure application of GABA into stratum pyramidale and stratum radiatum produced membrane hyperpolarization and depolarization, respectively. Pyramidal neurons in slices from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(111 citation statements)
references
References 34 publications
8
101
1
Order By: Relevance
“…Late developmental changes in the efficacy of inhibition is not unique to the developing LGNd, but has also been reported in neocortex (Luhmann and Prince, 1990;Agmon and O'Dowd, 1993;Burgard and Hablitz, 1993) hippocampus (Harris and Teyler, 1983;Mueller et al, 1984;Swann et al, 1989), and piriform cortex (Schwab et al, 1984). Thus, late functional maturation of inhibitory connectivity may represent a general mech- Figure 6.…”
Section: Discussionmentioning
confidence: 87%
“…Late developmental changes in the efficacy of inhibition is not unique to the developing LGNd, but has also been reported in neocortex (Luhmann and Prince, 1990;Agmon and O'Dowd, 1993;Burgard and Hablitz, 1993) hippocampus (Harris and Teyler, 1983;Mueller et al, 1984;Swann et al, 1989), and piriform cortex (Schwab et al, 1984). Thus, late functional maturation of inhibitory connectivity may represent a general mech- Figure 6.…”
Section: Discussionmentioning
confidence: 87%
“…34, 469,470). Some of the early reports of this phenomenon were of experiments done in hippocampus (430,431). That spontaneous activity in hippocampus depends on excitatory GABA transmission is apparent from both the effects of GABA A blockers on activity (see above) and from the fact that the developmental disappearance of spontaneous GDPs parallels closely the switchover to inhibitory GABA A action (283).…”
Section: Relationship To Channel Developmentmentioning
confidence: 99%
“…34, 469, 470). It has been known for some time that GABA action was depolarizing and functionally excitatory in many developing neurons (35,44,307,353,355,359,430,431,446). Experiments using the gramicidin perforated patch method of whole cell recording, which does not disrupt intracellular chloride levels, subsequently showed that the excitatory action of GABA was not caused by a unique GABA receptor, but by elevated intracellular Cl Ϫ concentrations early in development (468,505).…”
Section: Different Immature Channel Function Due To Different Ion mentioning
confidence: 99%
“…Previous studies have shown that GABAergic neurons are born prenatally (Schlessinger et al, 1978;Amaral and Kurz, 1985;Lubbers et al, 1985), and by the end of the first postnatal week, they make synaptic contacts on granule cell dendrites as well as somata (Lubbers and Frotscher, 1988;Ribak, 1988, 1990). Although GABAergic responses have been shown to occur in developing hippocampal and cortical pyramidal cells (Mueller et al, 1984;Kriegstein et al, 1987;Janigro and Schwartzkroin, 1988;Ben-Ari et al, 1989;Gaiarsa et al, 1990;Blanton and Kriegstein, 1991;Luhmann and Prince, 1991;Zhang et al, 1991;Hosokawa et al, 1994;Fleidervish and Gutnick, 1995), the functional properties of the early GABA A receptormediated synaptic transmission in the late-developing dentate granule cells are not well understood. The data presented here demonstrate that the overwhelming majority of dentate granule cells of the early postnatal rat possess functionally active GABAergic synaptic inputs [interestingly, no glutamatergic synaptic events can be observed at this time in granule cells (our unpublished observations)], similar to CA1 and CA3 pyramidal cells (Ben-Ari et al, 1989;Hosokawa et al, 1994;Gaiarsa et al, 1995).…”
Section: Early Functional Gabaergic Synapses On Immature Granule Cellsmentioning
confidence: 99%